Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Connect with a community of experts ready to help you find solutions to your questions quickly and accurately. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

Write the slope-intercept form of the equation of the line through the given point with the
given slope.
through: (2,-2), slope = -5/6


Sagot :

Answer:

[tex]\rm y = -\dfrac{5}{6} x-\dfrac{1}{3}[/tex]

Step-by-step explanation:

The slope intercept form of a line equation is

y = mx + b where m is the slope and b the y-intercept

Slope is given as [tex]- \dfrac{5}{6}[/tex]

So equation of line is
[tex]\rm y = -\dfrac{5}{6}x + b\\\\We\;can\;find\;bby\;substituting\;the\;x,\;y\;values\;for\;point\;(2,\;-2)\;into\;the\;equation\\\rm y = -\dfrac{5}{6}x + b\\\\\\\rm We\;can\;find\;by\;substituting\;the\;x,\;y\;values\;for\;point\;(2,\;-2)\;into\;the\;equation\\\\-2 = -\dfrac{5}{6}\times2 + b\\\\-2 = -\dfrac{10}{6} + b\\\\-2 = -\dfrac{5}{3} + b\\\\[/tex]

[tex]\rm Adding\;\dfrac{5}{3} \;to\;both\;sides\;:\\\dfrac{5}{3} - 2 = b\\\\\dfrac{5-6}{3} = b\\\\b = -\dfrac{1}{3}[/tex]

So equation of line is
[tex]\rm y = -\dfrac{5}{6} x-\dfrac{1}{3}[/tex]

Answer:

[tex]\huge\boxed{y=-\frac{5}{6}x-\frac{1}{3}}[/tex]

Useful Information:

The equation of a straight line: [tex]y=mx+c[/tex]

Step-by-step explanation:

To work this out you would first need to substitute the gradient into the equation, this gives you[tex]y=-\frac{5}{6}x+c[/tex].

The next step is to substitute the x and y coordinates from the point (2,-2) into the equation, this gives you [tex]-2=-\frac{5}{6}(2)+c[/tex]

In order to work out the value of c, you would have to bring the value of [tex]-\frac{5}{6}(2)[/tex] over to the other side, this can be done by adding [tex]\frac{5}{6}(2)[/tex] or [tex]-\frac{5}{3}[/tex] to -2, which gives you [tex]-\frac{1}{3}[/tex].

The final step is to substitute the m value of  [tex]-\frac{5}{6}[/tex] and the c value of  [tex]-\frac{1}{3}[/tex] into the equation, this gives you [tex]y=-\frac{5}{6}x-\frac{1}{3}[/tex]

1) Substitute the gradient.

[tex]y=-\frac{5}{6}x+c[/tex]

2) Substitute the x and y coordinates.

[tex]-2=-\frac{5}{6}(2)+c[/tex]

3) Bring [tex]-\frac{5}{6}(2)[/tex] over to the other side.

[tex]c=-2+\frac{5}{6}(2)[/tex]

4) Simplify to find the value of c.

[tex]c=-\frac{1}{3}[/tex]

5) Substitute the m and c values.

[tex]y=-\frac{5}{6}x-\frac{1}{3}[/tex]

Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.